PENGARUH ASET TIDAK BERWUJUD DAN KEPEMILIKAN PUBLIK TERHADAP NILAI PERUSAHAAN YANG TERDAFTAR DALAM INDEK LQ 45 PERIODE TAHUN 2016 – 2020 - Kasman Kasman (Universitas Sahid, 2022)
This study aims to determine the effect of intangible assets and public ownership on the value of companies listed in the LQ 45 Index on the Indonesia Stock Exchange for the 2016-2020 period. The method of data collection in this study was indirect observation, only examining the object of research, namely manufacturing companies listed on the Indonesia Stock Exchange, precisely on the LQ 45 Index. Observations made by researchers were non-participant observations, where researchers made observations as data collectors without involving themselves. or become part of the observed environment. This study obtained empirical results that became evidence of the Effect of Intangible Assets and Public Ownership on the Value of Companies Listed in the LQ 45 Index for the Period of 2016 – 2020. Based on the analysis, it can be concluded that there is no simultaneous effect of Intangible Assets (X1) and Ownership. Public (X2) to Firm Value (Y). There is no partial significant effect of Intangible Assets (X1) on Firm Value (Y). There is no partial significant effect of Intangible Assets (X1) on Firm Value (Y).Keywords : Intangible Assets, Public Ownership, Company Value